Predictor Variables Affecting Adoption of Improved Pig Management Practices by Entrepreneurs (Indian Journal of Extension Education, 2021)
In order to transform a traditional pig farmer in to an entrepreneur, one will require some specific traits. Study was carried out to find out significant predictor variables affecting adoption of improved pig management practices by entrepreneur. The present study was conducted in Jharkhand and Chhattisgarh having three agroclimatic regions each. Total 60 large commercial pig farmers were selected from six districts of two states. The effect of socio-economic and entrepreneurial characteristics was analyzed on adoption of improved pig management practices. It was found that 57 per cent variation was due to five significant predictor variables namely decision-making ability, mass media exposure, rearing experience, credit utilization and family size. Extension officers, veterinary personnel, gram panchayats and other related functional units have to play a key role in giving a definite shape to make this endeavor into a reality.